The Political Function for Twitter: Analytical study in the content of talks the Iraqi Politicians during the Electoral Crisis 2021 - ALFAHAD, ASMAA HASHIM SALIM SARIH (Al-Adab Journal, 2022)
The new social media, represented by the Twitter, has entered the field of communication strongly, and it has become one of the important and effective elements in political life, especially in times of crises, conflicts and election seasons. Leaders and political leaders have used social media to achieve their political goals by communicating with their masses and moving public opinion towards their goals and against the movements their opponents, and many of them succeeded in using Twitter during the election campaigns to mobilize support for their programs and direct criticism to the opponents' programs. This research deals with the political function of the Twitter through an analytical study of the tweets of Iraqi politicians from leaders of political blocs and parties published on Twitter website about the ramifications that followed the parliamentary elections in Iraq on the tenth of October, 2021 The research used the content analysis method as a systematic method in analyzing sample data.The research, also used the content categories form as a tool for data collection, and came up with the results.